Natural Compounds as a Therapeutic Intervention following Traumatic Brain Injury: The Role of Phytochemicals - Scheff, Stephen W. (J Neurotrauma, 2017)
There has been a tremendous focus on the discovery and development of neuroprotective agents that might have clinical relevance following traumatic brain injury (TBI). This type of brain injury is very complex and is divided into two major components. The first component, a primary injury, occurs at the time of impact and is the result of the mechanical insult itself. This primary injury is thought to be irreversible and resistant to most treatments. A second component or secondary brain injury, is defined as cellular damage that is not immediately obvious after trauma, but that develops after a delay of minutes, hours, or even days. This injury appears to be amenable to treatment. Because of the complexity of the secondary injury, any type of therapeutic intervention needs to be multi-faceted and have the ability to simultaneously modulate different cellular changes. Because of diverse pharmaceutical interactions, combinations of different drugs do not work well in concert and result in adverse physiological conditions. Research has begun to investigate the possibility of using natural compounds as a therapeutic intervention following TBI. These compounds normally have very low toxicity and have reduced interactions with other pharmaceuticals. In addition, many natural compounds have the potential to target numerous different components of the secondary injury. Here, we review 33 different plant-derived natural compounds, phytochemicals, which have been investigated in experimental animal models of TBI. Some of these phytochemicals appear to have potential as possible therapeutic interventions to offset key components of the secondary injury cascade. However, not all studies have used the same scientific rigor, and one should be cautious in the interpretation of studies using naturally occurring phytochemical in TBI research.